2008
DOI: 10.1083/jcb.200711165
|View full text |Cite
|
Sign up to set email alerts
|

The tight junction protein complex undergoes rapid and continuous molecular remodeling at steady state

Abstract: The tight junction defines epithelial organization. Structurally, the tight junction is comprised of transmembrane and membrane-associated proteins that are thought to assemble into stable complexes to determine function. In this study, we measure tight junction protein dynamics in live confluent Madin–Darby canine kidney monolayers using fluorescence recovery after photobleaching and related methods. Mathematical modeling shows that the majority of claudin-1 (76 ± 5%) is stably localized at the tight junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
354
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(391 citation statements)
references
References 68 publications
24
354
1
1
Order By: Relevance
“…Under basal conditions, when MLCK is active (11), steadystate exchange of tight junction-associated claudin-1, occludin, ZO-1, and actin in Caco-2 monolayers was comparable to that reported previously in MDCK cells (3). MLCK inhibition only affected exchange of ZO-1, which was profoundly reduced.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Under basal conditions, when MLCK is active (11), steadystate exchange of tight junction-associated claudin-1, occludin, ZO-1, and actin in Caco-2 monolayers was comparable to that reported previously in MDCK cells (3). MLCK inhibition only affected exchange of ZO-1, which was profoundly reduced.…”
Section: Discussionsupporting
confidence: 77%
“…These and other observations drove development of models that depicted the tight junction as a static, heavily cross-linked protein complex (2). However, recent data showing rapid and continuous remodeling of the tight junction refuted the previous models and led to the hypothesis that modulation of protein remodeling behavior could be a mechanism of tight junction barrier regulation (3,4).…”
mentioning
confidence: 99%
“…Studies using fluorescence recovery after photobleaching (FRAP) analysis have found that the turnover of proteins in tight junction strands is much shorter than previously thought (Shen et al, 2008). It has been reported that Cldn5 has a relatively short half-life and can be polyubiquitylated in the membrane, tagging it for degradation (Mandel et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Occludin has been linked to the regulation of paracellular permeability of small hydrophilic molecules across cultured epithelial monolayers Schneeberger and Lynch, 2004); it is thought that this regulatory mechanism involves phosphorylation events as well as the actin cytoskeleton because the C-terminal domain of occludin binds to protein kinases and lipid kinases, as well as to actin filaments and cytoskeletal linkers (Aijaz et al, 2006;Schneeberger and Lynch, 2004). Strikingly, live-cell-imaging experiments using GFP-tagged occludin have recently suggested that occludin diffuses within the junction, suggesting that occludin dynamics might contribute to paracellular diffusion (Shen et al, 2008). However, because the experiment involved an N-terminal GFP-tag and blocking the Nterminus is known to interfere with anchoring of occludin within the junction, it is not clear whether the observed dynamic properties indeed reflect physiological occludin behaviour (Huber et al, 2000).…”
Section: Paracellular Permeabilitymentioning
confidence: 99%